INVITRO PHYTOCHEMICAL ANALYSIS AND ANTIOXIDANT ACTIVITY OF ARGEMONE MEXICANA - Lokeshwar.T; Sathish Sankar* (Chelonian Research Foundation, 2023)
This research aimed to investigate the phytochemical composition and antioxidant potential of Argemone Mexicana, a medicinal plant with diverse traditional uses. The study employed in vitro methods to analyze the phytochemical constituents and assess the antioxidant activity of various extracts from Argemone Mexicana.The phytochemical analysis revealed the presence of bioactive compounds such as alkaloids, flavonoids, phenols, tannins, and saponins. These compounds are known for their therapeutic properties and may contribute to the plant's medicinal efficacy. Additionally, the study assessed the antioxidant activity of Argemone Mexicana extracts using established assays, including DPPH radical scavenging and ferric reducing antioxidant power (FRAP). The results demonstrated significant antioxidant potential, suggesting that Argemone Mexicana possesses compounds capable of neutralizing free radicals and preventing oxidative stress.Furthermore, the research explored the correlation between phytochemical content and antioxidant activity, providing valuable insights into the potential health benefits of Argemone Mexicana. The findings highlight the plant's promising role as a natural source of antioxidants, supporting its traditional use in folk medicine and emphasizing its potential applications in pharmaceutical and nutraceutical industries. This research contributes to the understanding of the pharmacological properties of Argemone Mexicana and underscores its significance in the development of novel therapeutic agents. Keywords: Argemone Mexicana, antioxidant, phytochemicals, DPPH radicals, Health, Well-being, Diseases, Medical, Healthy lives